RANCANG BANGUN APLIKASI MOBILE LEARNING PADA SISTEM OPERASI ANDROID - , YOLANDA SRI RAHAYU, Dr. Azhari SN, M.T ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Currently, smartphones and tablets become a very common tool used in everyday life. The use of those tools have been covering various aspects of life such as work, entertainment, commerce and education. Because of the frequent use of smartphones for learning facility, the interest in mobile learning is heating up. Mobile learning is a learning model that utilizes mobile devices such as mobile phones, PDAs, laptops, and tablet PCs. Mobile learning application development is still minim, where there is limited user roles. Therefore, a mobile learning application that provides learning facilities where the user can play an active role is needed. The application is developed in Android platform. This research developed a mobile learning application on Android operating system that can help users, especially among college students as a means to support learning in the classroom. In the development process, this study using the MVC pattern (Model, View, Controller) for implementation on the server side. Based on test results, the application has two different modes according to the design, namely student mode and lecturer mode. Student mode displays a list of materials, downloading material files, a list of assignment, sending answer with the option to upload file if necessary, downloading grades file when it is available, participate in forums and receive an email whenever there is a new assignment or new grades. Lecturer mode displays a list of material with the options to upload a file material, adding assignment, viewing a list of answers that have been posted, uploading a grades file if the assignment has been checked and participate in forum. Administrator can confirm the user who has registered, change the role of each user, add courses, deleting course, editting course, adding members to the course, and remove member from the course.